First record of Histiotus laephotis (Thomas, 1916) from Chile and new distributional information for Histiotus montanus (Phillipi and Landbeck, 1861) (Chiroptera, Vespertilionidae) - Ossa, Gonzalo (2015)
We report new distributional records for Histiotus montanus and first records of Histiotus laephotis for Chile. Morphological measurements and analyses of echolocation calls confirm the differences between the species. Histiotus montanus has a smaller forearm (49.7±0.8 vs. 51.7±0.4 mm) and darker and shorter ears than H. laephotis; the latter has a yellowish fur in contrast to other Histiotus species. Acoustic analyses showed significant differences between the species: H. laephotis have shorter pulses (1.3±0.4 vs. 3.6±2.6 ms), with lower start and peak frequencies (start frequency 38.2±2.6 vs. 46.4±4.6 kHz; peak frequency 30.4±3.7 vs. 32.1±2.2 kHz) than H. montanus. These findings place the Tarapacá region of northern Chile as the most diverse in terms of bat species in the country. Furthermore, these results increase the total number of bat species known to occur in the country to 13.